Early Parodies of Arthur Conan Doyle’s Sherlock Holmes Stories: Charles C. Rothwell’s “Adventures of Sherwood Hoakes: An Interrupted Honeymoon”(1892) and A. Dewar Willock’s “A Study in Red” (1892) as Criticism and Homage - Urszula Żoczek (Polish Journal of English Studies)
he main objective of this paper is to explore how parody operates within, and engages with, the genre of detective fiction. By treating the selected texts as a form of literary review of Arthur Conan Doyle’s works, the focus of the paper is on the analysis of the reception of Doyle’s Sherlock Holmes stories as carried out through the parodies and pastiches of the Great Detective. While a number of classifications of detective fiction have been proposed, little has been said about the genre’s relationship with parody. Similarly, the figure of Sherlock Holmes, arguably the most influential creation within the genre, has rarely been analyzed in this context. Although many scholars acknowledge parodies and pastiches as a reflection of the popularity of the character, few of those texts, especially those created as an early response to Doyle’s works, have been discussed. This paper examines two such texts – Charles C. Rothwell’s “Adventures of Sherwood Hoakes: An Interrupted Honeymoon” and A. Dewar Willock’s “A Study in Red,” a parody and a pastiche respectively – which, although included in collections of parodies and pastiches, have not yet been examined in any capacity. Parody, understood both as an element of the structure of detective fiction and as a commentary on its conventions, serves as a tool for examining selected texts which constituted early responses to Doyle’s work. This paper analyzes the texts as a means of literary criticism, in which the parodic device has been utilized to reflect the attitudes of Doyle’s contemporaries toward his stories, demonstrating how parodic device can be used both as a vehicle for criticism and as a means of paying homage to the co-creator of the genre.